2010
DOI: 10.1002/jmr.1009
|View full text |Cite
|
Sign up to set email alerts
|

Selective probing of a NADPH site controlled light‐induced enzymatic catalysis

Abstract: Achieving molecular recognition of NADPH binding sites is a compelling strategy to control many redox biological processes. The NADPH sites recognize the ubiquitous NADPH cofactor via highly conserved binding interactions, despite differences in the regulation of the hydride transfer in redox active proteins. We recently developed a photoactive NADPH substitute, called nanotrigger NT synchronizing the initiation of enzymatic catalysis of the endothelial NO-synthase (eNOS) with a laser pulse. Spatial and tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…NS1 competed with NADPH on nNOS reduction in a dose-dependent manner, presenting a typical saturation curve, and led to an apparent inhibition constant K i ¼ 15 AE 4 μM. This value compares well with those obtained previously with NT1, K i ¼ 7 AE 3 μM (13,17), showing that NS1 and NT1 display similar affinities for the NADPH site of constitutive NOS, as suggested by our molecular modelling study.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…NS1 competed with NADPH on nNOS reduction in a dose-dependent manner, presenting a typical saturation curve, and led to an apparent inhibition constant K i ¼ 15 AE 4 μM. This value compares well with those obtained previously with NT1, K i ¼ 7 AE 3 μM (13,17), showing that NS1 and NT1 display similar affinities for the NADPH site of constitutive NOS, as suggested by our molecular modelling study.…”
Section: Resultssupporting
confidence: 88%
“…This choice of a shorter stilbene moiety was guided by initial modelling studies, which had suggested that a shorter compound than NT1 with the same terminal donor group could fit tighter to this site. Our design retained the nucleotidic recognition motif of NADPH that confers proper targeting to the NADPH site, based on previous studies that led to the discovery of NT1 (12)(13)(14)17). The designed inhibitor NS1 was docked in nNOS red by replacement of the embedded NADPH (4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rational way to regulate redox stress would be to make use of compounds modulating NADPH levels, which requires selectivity toward specific NADPH-dependent enzymes without strong interference with normal cellular processes. Recently, we designed a novel photoactive probe, called nanoshutter (NS1) that efficiently bound to constitutive NOS (eNOS and nNOS) [19] in a similar manner than our previously reported dienic nanotrigger [2023]. NS1 reversibly inhibited NO formed by recombinant eNOS in endothelial cells by competing with NADPH binding and presented anti-angiogenic effects [19].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting structure was refined by allowing the system to relax over molecular dynamics (MD) simulation. The model was further tested by Verify 3D and Ramachandran plots [23].…”
Section: Homology Modelingmentioning
confidence: 99%